2012
DOI: 10.4236/pp.2012.34066
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and Role of High Loading Dose Clopidogrel in Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention

Abstract: Antiplatelet therapy, which reduces platelet activation and aggregation, is the corner stone of treatment for patients undergoing percutaneous coronary intervention (PCI). Clopidogrel is an established oral antiplatelet medication of thienopyridine class, which inhibits blood clots in coronary artery disease, peripheral vascular disease, and cerebrovascular disease. Many studies have revealed that high loading dose clopidogrel in patients undergoing PCI. This review article investigates the rationale and role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In contrast to normal volunteers and stable coronary disease patients, the IPA by P2Y12 receptor inhibitors is delayed for several hours especially in STEMI patients, but also in NSTEMI patients (10)(11)(12)(13)(14)(15)(22)(23)(24). Therefore, some patients continue to demonstrate inadequate IPA in the early hours after LD administration, particularly at 1 and 2 h following the LD, a state associated with a higher risk of thrombotic events (16,25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to normal volunteers and stable coronary disease patients, the IPA by P2Y12 receptor inhibitors is delayed for several hours especially in STEMI patients, but also in NSTEMI patients (10)(11)(12)(13)(14)(15)(22)(23)(24). Therefore, some patients continue to demonstrate inadequate IPA in the early hours after LD administration, particularly at 1 and 2 h following the LD, a state associated with a higher risk of thrombotic events (16,25).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in patients with stable coronary artery disease ticagrelor achieves more rapid and greater IPA than a high loading dose of clopidogrel (10). In more recent studies it has been shown that, contrary to normal volunteers and patients with stable coronary artery disease, when administrating a P2Y12 inhibitor, the time to peak IPA may take up to 4 h in patients with ACS and even longer in patients with ST-elevation myocardial infarction (STEMI) (11)(12)(13)(14)(15). This delay in platelet inhibition in response to a ticagrelor loading dose (LD) has been related primarily to a drugdrug interaction, impaired intestinal absorption and increased platelet turn-over, associated with ACS as well as to the type of myocardial infarction, advanced age and diabetes mellitus (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STEMI is a type of ACS (acute coronary syndrome) 1 . Thin fibrous cap with large lipid core and inflammation of atherosclerotic plaque may result in plaque fissuring.…”
Section: Introductionmentioning
confidence: 99%